Mengenalkan Anak pada Dunia Film - Satya Indra Karsa (MediaTor (Jurnal Komunikasi), 2006)
According to research conducted by Yayasan Kesejahteraan Anak Indonesia (Indonesian Children Wealth Foundation—YKAI), children spent their times in front of TV more than 20-25 hours/week, or 3-4 hours/day. Another research stated that children viewing habit reached a relatively high exposure. Based on these facts, this article speaks about the importance to teach children how to appreciate lesson films and other audiovisuals. The process included several steps, such as an introduction to the duty and responsibility of media worker or film maker toward their masterpiece and their audience, reading critics and reference to reduce disappointment if someone meets an underdeveloped or low quality film.